UV LEDs based on p–i–n core–shell AlGaN/GaN nanowire heterostructures grown by N-polar selective area epitaxy *Contribution of an agency of the US government; not subject to copyright. (21st March 2019) - Brubaker, Matt D; Genter, Kristen L; Roshko, Alexana; Blanchard, Paul T; Spann, Bryan T; Harvey, Todd E; Bertness, Kris A
Abstract: Ultraviolet light-emitting diodes fabricated from N-polar AlGaN/GaN core–shell nanowires (NWs) with p – i – n structure produced electroluminescence at 365 nm with ∼5× higher intensities than similar GaN homojunction LEDs. The improved characteristics were attributed to localization of spontaneous recombination to the NW core, reduction of carrier overflow losses through the NW shell, and elimination of current shunting. Poisson-drift-diffusion modeling indicated that a shell Al mole fraction of x  = 0.1 in Al x Ga1− x N effectively confines electrons and injected holes to the GaN core region. AlGaN overcoat layers targeting this approximate Al mole fraction were found to possess a low-Al-content tip and high-Al-content shell, as determined by scanning transmission electron microscopy. Photoluminescence spectroscopy further revealed the actual Al mole fraction to be NW diameter-dependent, where the tip and shell compositions converged towards the nominal flux ratio for large diameter NWs.